ANALISIS SISTEM PENGENDALIAN INTERNAL TERHADAP TUNJANGAN KINERJA POLDA MALUKU - MEIDYLISA PATTY (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2019)
Performance allowances are given as rewards or rewards for employees and those with good performance. This research aims to know, analyze and compare the process of providing the performance allowance of members of the Maluku Polda with the common SPI reference framework of COSO. This research is a mixed study that uses primary and secondary data. Secondary Data is sourced on research-related documents and results in research questionnaire responses calculated based on the formula. Secondary data will clarify primary data i.e. survey results and interviews related to research issues.The results showed that the Moluccas and Satkers have adopted a system of control over the performance allowance but there is still weakness in its application so that the Maluku police are expected to re-evaluate the performance allowance control system based on the COSO reference framework or provide clear flowcharts and job description for its ranks.